Davidson on communication and languages: A reexamination (2018)
In order to evaluate the validity and implications of Donald Davidson’s arguments against the need for conventions in order for linguistic communication (or, more generally, against the need to postulate language as an entity in order to account for communication), the theoretical considerations behind his conclusions are traced through several of his essays. Once Davidson’s ideas on communication, radical interpretation, and the lack of strict nomological connections between physical and mental events have been pointed out as necessary for his argument, it will be seen that these imply the need for something very close to linguistic conventions. The article closes by considering a few possible counterarguments this last conclusion.